Optimizing Family Role in Hypertension Management Through Education and Self-Monitoring - Hijrah Hijrah; Hasbullah Ulla; Ramluddin Udin; Nurwasilah Nurwasilah (SWAGATI : Journal of Community Service, 2025)
Hypertension is a chronic condition that requires routine management to prevent long-term complications. One effective strategy is home blood pressure monitoring by patients with family support. This community service activity aimed to improve family knowledge and technical skills in performing self-monitoring of blood pressure for hypertensive patients. The program was conducted in a single session with 20 patients and their family members. The intervention included interactive education and hands-on training using digital sphygmomanometers. Evaluation was conducted through pre- and post-tests for knowledge, along with observation of self-monitoring skills. The results showed a significant increase in family knowledge scores from an average of 45% to 78%, with the majority of participants in the high category. Self-monitoring skills also improved, with 14 participants rated as good, 5 as moderate, and 1 as poor. These findings indicate that a single intensive educational and practical session effectively enhances family capabilities as active partners, emphasizing the importance of self-monitoring blood pressure in supporting home management of hypertension. It is recommended to continue with follow-up or refresher sessions to maintain skills and consistency in blood pressure monitoring at home.